Determinan Kesiapan Mahasiswa Keperawatan dalam Menghadapi Situasi Gawat Darurat - Ayu Wahyuni Lestari; Sri Yuliana; Ineke Noviana; Nur Ramadhan; Martha Meti Kody (JUKEJ : Jurnal Kesehatan Jompa, 2026)
Readiness of nursing students to manage emergency situations is a crucial competency prior to entering professional clinical practice. Several factors are presumed to influence readiness, including self-efficacy, academic achievement, and demographic characteristics. However, empirical evidence regarding the determinants of student readiness remains inconsistent. This study aimed to analyze the determinants of nursing students’ readiness in managing emergency situations by examining the roles of self-efficacy, Grade Point Average (GPA), gender, age, and living arrangements. A quantitative study with a cross-sectional analytic design was conducted among 56 nursing students selected using total sampling. Self-efficacy and readiness were measured using structured Likert-scale questionnaires and analyzed as numerical scores. Data analysis included Pearson correlation, Independent t-test, One-Way ANOVA, and multiple linear regression with a significance level set at p < 0.05. The mean self-efficacy score was 44.54 (SD = 6.14), while the mean readiness score was 55.52 (SD = 6.79). No significant correlation was found between self-efficacy and readiness (r = 0.18; p = 0.18). GPA showed a significant difference in readiness (p = 0.01), with students having GPA >3.50 demonstrating higher readiness levels. Gender, age, and living arrangements were not significantly associated with readiness (p > 0.05). Multiple linear regression analysis indicated that the overall model was significant (p = 0.03), with GPA emerging as the primary determinant of readiness (β = 0.32; p = 0.01). GPA is a significant determinant of nursing students’ readiness to manage emergency situations, whereas self-efficacy and demographic factors were not significantly associated. Strengthening academic performance may contribute to improving students’ clinical readiness.